2020
DOI: 10.26434/chemrxiv.11833323.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D Convolutional Neural Networks and a CrossDocked Dataset for Structure-Based Drug Design

Abstract: One of the main challenges in drug discovery is predicting protein-ligand binding affinity. Recently, machine learning approaches have made substantial progress on this task. However, current methods of model evaluation are overly optimistic in measuring generalization to new targets, and there does not exist a standard dataset of sufficient size to compare performance between models. We present a new dataset for structure-based machine learning, the CrossDocked2020 set, with 22.5 million poses of ligands dock… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…We found agreement of MedusaDock E without VDWR and NeuralDock E without VDWR with experimental pK, with similar correlations for both tools (r=-0.48 for both, p<0.0001), and no statistically significant difference in correlations with 2-way ANCOVA (F=1.27, p=0.26), (Figure 3b). The correlation of MedusaDock E without VDWR with experimental pK (r=−0.48) is comparable to that of AutoDock Vina scoring (r=0.41) as reported in Francoeur et al 23 , with MedusaDock performing better, likely due to our extensive sampling and computational effort for each protein-ligand pair. NeuralDock predicts experimental pK better than MedusaDock on the validation set (Figures 1b, 1c, 3b), however experimental validation of the pKs is needed to confirm that this result holds for SOD1 and other proteins.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…We found agreement of MedusaDock E without VDWR and NeuralDock E without VDWR with experimental pK, with similar correlations for both tools (r=-0.48 for both, p<0.0001), and no statistically significant difference in correlations with 2-way ANCOVA (F=1.27, p=0.26), (Figure 3b). The correlation of MedusaDock E without VDWR with experimental pK (r=−0.48) is comparable to that of AutoDock Vina scoring (r=0.41) as reported in Francoeur et al 23 , with MedusaDock performing better, likely due to our extensive sampling and computational effort for each protein-ligand pair. NeuralDock predicts experimental pK better than MedusaDock on the validation set (Figures 1b, 1c, 3b), however experimental validation of the pKs is needed to confirm that this result holds for SOD1 and other proteins.…”
Section: Resultssupporting
confidence: 85%
“…Due to the inclusion of protein-small molecule crystal structures, K DEEP is biased and has limited generalizability to proteins not bound to small molecules. This issue of bias has been discussed in Francoeur et al 23 and arises from self-docking, in which the neural network is provided with a low conformational energy crystal structure as input, and therefore does not perform conformational sampling. Cang et al 26 use convolutional networks with manually constructed ligand features based on ligand topology, but provide no forward validation with docking tools; instead, only binding affinity is predicted, increasing the risk of overfitting and self-docking bias.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Francoeur et al . [ 8 ] have found that data augmentation with low quality re-docking data can improve model performance. Despite the caution from the authors that the improvement might have resulted from the expanded data volume, their report shows that data augmentation with structural information improve the predicting power of a model.…”
Section: Introductionmentioning
confidence: 99%